1989
DOI: 10.1007/bf00175593
|View full text |Cite
|
Sign up to set email alerts
|

Effects of simulated acid rain on uptake, accumulation, and retention of fluoride in forage crops

Abstract: Forage crops accumulate F from exposures to the air pollutant HF and the rate and amount taken up can be affected by a number of external factors, one of which is precipitation. To assess how precipitation, including acidic precipitation, alters F uptake and retention in forage, alfalfa (Medicago sativa L. var. Saranac) and tall fescue (Festuca arundinacea Schreb. var. Kentucky 31) were subjected to extended exposures to HF and were treated periodically with various solutions (pH 5.6, 4.0, and 3.0) supplied as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

1990
1990
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 6 publications
1
3
0
Order By: Relevance
“…The finding that overhead irrigation with good-quality water reduced foliar F concentrations (at least somewhat) is similar to the observation of Maclean et al, who, in a study of lucerne and tall fescue grass (Festuca arundinacea) exposed to atmospheric F, also found that rainfall (or washing with detergent) reduced the foliar concentration of F. Several mechanisms may result in a decrease in tissue F concentrations, including growth dilution, leaf death, translocation, or volatilization, with the last mechanism considered a major contributor of F removal from plants . Therefore, to investigate this possibility, plants were grown without overhead irrigation for another 2 weeks following the irrigation with deionized water.…”
Section: Discussionsupporting
confidence: 88%
“…The finding that overhead irrigation with good-quality water reduced foliar F concentrations (at least somewhat) is similar to the observation of Maclean et al, who, in a study of lucerne and tall fescue grass (Festuca arundinacea) exposed to atmospheric F, also found that rainfall (or washing with detergent) reduced the foliar concentration of F. Several mechanisms may result in a decrease in tissue F concentrations, including growth dilution, leaf death, translocation, or volatilization, with the last mechanism considered a major contributor of F removal from plants . Therefore, to investigate this possibility, plants were grown without overhead irrigation for another 2 weeks following the irrigation with deionized water.…”
Section: Discussionsupporting
confidence: 88%
“…In any case, the derivation of dose-effect relationships from field data has been proved to be extremely difficult as a great number of internal and external factors as light intensity, air and soil temperature, relative humidity, winds and precipitation do not only affect fluoride accumulation but also symptom expression (Weinstein, 1977;O'Connor and Horsman, 1982;VDI, 1989). Furthermore, in the Cubat~o region gaseous fluoride compounds do not occur all by themselves but in combination with other pollutants as SO2, 03, NOx and hydrocarbons etc., which may affect fluoride accumulation as well as physiological reactions leading to less than additive, additive or synergistic effects (Mc Cune, 1982;Wilson, 1988, 1990;MacLean et al, 1989;Davieson et al, 1990;MacLean, 1990). Nevertheless, the dependence of plant response from all these factors underlines the main advantage of bioindicators as integrators of the various concentrations and conditions to which plants are exposed in the field (Guderian and Reidl, 1982;Weinstein and Laurence, 1989) thereby facilitating risk prognosis.…”
Section: Discussionmentioning
confidence: 94%
“…The extensive literature on this topic has been reviewed several times (see, e.g. Following uptake, fluorides may be leached, evaporated and possibly translocated out of the leaf (BENEDICT et al 1964;HITCHCOCK et al 1971;KRONBERGER 1981;DAVISON 1982;TAKMAZ-NISANCIOGLU and DAVISON 1982;GARREC and CHOPIN 1983;MACLEAN et al 1989), and so the net accumulation under field conditions is generally lower than the total uptake. The uptake depends on the concentration and composition of fluoride in ambient air and the duration of exposure, but it also varies with vegetation structure, plant species and growth conditions (JACOBSON et al 1966;McCUNE and HiTCHCOCK 1971;DAVISON and BLAKEMORE 1976).…”
Section: Introductionmentioning
confidence: 99%
“…The uptake depends on the concentration and composition of fluoride in ambient air and the duration of exposure, but it also varies with vegetation structure, plant species and growth conditions (JACOBSON et al 1966;McCUNE and HiTCHCOCK 1971;DAVISON and BLAKEMORE 1976). Following uptake, fluorides may be leached, evaporated and possibly translocated out of the leaf (BENEDICT et al 1964;HITCHCOCK et al 1971;KRONBERGER 1981;DAVISON 1982;TAKMAZ-NISANCIOGLU and DAVISON 1982;GARREC and CHOPIN 1983;MACLEAN et al 1989), and so the net accumulation under field conditions is generally lower than the total uptake.…”
Section: Introductionmentioning
confidence: 99%